Response of soil erosion to rainfall during different dry periods following drip irrigation - Zhang, Jinxin; Zhang, Dongdong; Zhang, Bin; Zeng, Shuyuan; Han, Zhen (Frontiers in Environmental Science, 2025)
Drip irrigation, a widely adopted water-saving technique, has received limited attention regarding its indirect effects on soil erosion. This study investigates soil erosion characteristics at varying intervals following drip irrigation using simulated rainfall experiments and an unirrigated control (S0) subjected to identical rainfall simulation procedures. The results showed significant hydrological differences between drip-irrigated and unirrigated treatments. Irrigated soils exhibited reduced runoff (mean reduction = 23.19%; p < 0.05) and sediment yield (mean reduction = 24.33%; p < 0.05) compared to S0, except for runoff in S24. Erosion mitigation was attributed to enhanced rainwater retention via surface irrigation-formed crusts and desiccation cracks generated during extended drying periods. These results highlight a previously under-characterized interaction between water-saving irrigation practices and soil erosion processes. The temporal evolution of soil surface characteristics following drip irrigation appears to influence hydrological responses during subsequent precipitation events, providing new insights for optimizing irrigation strategies in erosion-prone situations.